Franklin's school play - Bourgeois, Paulette; Clark, Brenda (New York : Scholastic, 1996)
Franklin is assigned a lead role in the class play, but he worries that his stage fright will keep him from performing well as the Nutcracker Prince.
Kliatt
3.5
K-3
Keywords: Acting -- Fiction; Schools -- Fiction; Turtles -- Fiction; Animals -- Fiction; Acting -- Fiction; School stories; Turtles -- Fiction; Animals -- Fiction